Metacognitive beliefs mediate the relationship between mind wandering and negative affect. (1st March 2017) - Carciofo, Richard; Song, Nan; Du, Feng; Wang, Michelle M.; Zhang, Kan
Abstract: Two studies ( Ns  = 254 and 130, aged 18–28) aimed to investigate associations between mind wandering and metacognitive beliefs, and whether these beliefs are involved in the relationship between mind wandering and negative affect. Participants completed questionnaire measures of metacognitive beliefs, mind wandering, daydreaming, negative affect, mindfulness, and sleep quality. Study 2 also included the Sustained Attention to Response Task, with thought-probe assessment of task-unrelated thought (mind wandering/daydreaming). The frequency of mind wandering/daydreaming/task-unrelated thought was found to positively correlate with the metacognitive dimensions of less cognitive confidence, more endorsement of belief in the uncontrollability/danger of thoughts, and more endorsement of belief in the need to control thoughts. Multiple-mediator analysis was undertaken with three main models where either mind wandering, daydreaming frequency, or task-unrelated thought was the predictor for negative affect. Metacognitive beliefs, mindfulness and sleep quality were simultaneously entered as potential mediators. Results showed that metacognitive belief in the uncontrollability/danger of thoughts was a consistently significant mediator, while mindfulness and sleep quality were less consistent. Overall, the current research indicates that metacognitive beliefs are an important consideration in the study of mind wandering/daydreaming, and a possibly key factor in understanding the association with negative affect. Highlights: New Chinese MCQ-30 scale showed validity and reliability. Mind wandering correlated with less cognitive confidence. Mind wandering correlated with belief in uncontrollable and dangerous thoughts. Metacognition mediated the association between mind wandering and negative affect.